2012
DOI: 10.1007/s00134-012-2565-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of creatine kinase is associated with worse outcomes in 2009 pH1N1 influenza A infection

Abstract: CK is a biomarker of severity in pH1N1 infection. Elevation of CK was associated with more complications and increased ICU LOS and healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 25 publications
0
25
2
2
Order By: Relevance
“…Although elevation of creatine kinase (CK) levels was seen in all patients, a higher degree of elevation was associated with worse outcomes. Elevations of CK in influenza infection are associated with longer duration of mechanical ventilation (15 days vs 11 days, P < .001) and longer median ICU length of stay (13 days vs 8 days, P = .01) . Seven patients had muscle biopsies obtained in their evaluation—one was normal and the other six demonstrated varying degrees of necrosis, regeneration, and edema—all of which can be consistent with a diagnosis of rhabdomyolysis.…”
Section: Resultsmentioning
confidence: 92%
“…Although elevation of creatine kinase (CK) levels was seen in all patients, a higher degree of elevation was associated with worse outcomes. Elevations of CK in influenza infection are associated with longer duration of mechanical ventilation (15 days vs 11 days, P < .001) and longer median ICU length of stay (13 days vs 8 days, P = .01) . Seven patients had muscle biopsies obtained in their evaluation—one was normal and the other six demonstrated varying degrees of necrosis, regeneration, and edema—all of which can be consistent with a diagnosis of rhabdomyolysis.…”
Section: Resultsmentioning
confidence: 92%
“…Unfortunately, risk factors to identify patients at high risk for ARDS development are still matter of research [14]. Sometimes, depending on the type of virus responsible for the pneumonia, viral infection can extend beyond the lung tissue; it was observed that an increase of plasmatic creatine kinase in patients with pH1N1 pneumonia is associated with higher mortality, suggesting myocarditis as potential explanation for the increase of creatine kinase [15].…”
mentioning
confidence: 99%
“…A multicenter report of patients admitted to the intensive care units found that creatinine kinase was elevated in 24%, with greater risk of renal replacement therapy and prolonged ventilation. 10 In vitro studies suggest that muscle cells also express the a2,3 and a2,6-linked sialic acid receptors, identical to the receptors influenza use to bind respiratory epithelial cells. 11 Rhabdomyolysis, therefore, seems to likely be a manifestation of viremia.…”
Section: Extrarespiratory Involvementmentioning
confidence: 99%